The dogs of war - Forsyth, Frederick, 1938- (New American Library, 2012)
In a remote corner of the impoverished African republic of Zangaro lies Crystal Mountain. At certain times of the day, the mountain itself seems to glow with a strange light. Only the ruthless and untouchable tycoon Sir James Manson knows why: the mountain contains billions of dollars worth of the world<U+2019>s most valuable mineral<U+2014>platinum. And he wants it all. To do so, he must first remove the unfriendly government currently in power and replace it with a puppet regime. Towards this end, Manson hires the deadly Cat Shannon and his team of mercenaries to do the dirty work. But he didn<U+2019>t realize how bloody things were going to get. And when he betrays the mercenaries to a brutal fate, he doesn<U+2019>t realize how far Shannon is willing to go for revenge<U+2026>